Edukasi Video Animasi Gerogi Terhadap Perilaku Menyikat Gigi Anak Di Puskesmas Cina Kabupaten Bone (Window of Public Health Journal, 2026)
Inappropriate toothbrushing behavior remains one of the causes of high rates of dental and oral health problems in children. Animated video education is expected to improve tooth-brushing behavior because it is more engaging and easier for children to understand. This study aims to analyze the effect of the GEROGI (Gerakan Gosok Gigi) animated video on tooth-brushing behavior among children aged 6–12 years in the working area of the Cina Community Health Center (UPT), Bone Regency. This study is quantitative, with a quasi-experimental design and a one-group pretest-posttest design. A sample of 38 children was selected using a purposive sampling technique. Data were collected using a structured questionnaire and analyzed using the Wilcoxon Signed-Rank Test at a 95% confidence level. The results showed that 35 respondents (92.1%) experienced an increase in tooth-brushing behavior scores after receiving the GEROGI animated video intervention. The results of the Wilcoxon Signed-Rank test showed a significant difference in tooth-brushing behavior scores before and after the intervention (p < 0.05). It was concluded that dental and oral health education through the GEROGI animated video was effective in increasing toothbrushing behavior among children aged 6–12 years in the working area of the Cina Community Health Center UPT, Bone Regency.